On Brazil's Term Structure : Stylized Facts and Analysis of Macroeconomic Interactions - Cabral, Rodrigo (IMF Working Papers; Working Paper ;, 2011)
This paper characterizes the term structure of Treasury bond yields for Brazil, and estimates a Nelson-Siegel Model to reproduce its stylized facts for the period 2004-2010. For this purpose, this paper uses a software developed by Fund staff. In addition, the paper estimates two versions of the Nelson-Siegel Model that incorporates macroeconomic variables with the aim of assessing the dynamic interactions between the yield curve and the macroeconomy.